Epigenetic regulation by G9a/GLP complex ameliorates amyloid‐beta 1‐42 induced deficits in long‐term plasticity and synaptic tagging/capture in hippocampal pyramidal neurons - Sharma, Mahima (Aging Cell, 2017)
Altered epigenetic mechanisms are implicated in the cognitive decline associated with neurodegenerative diseases such as in Alzheimer's disease (AD). AD is the most prevalent form of dementia worldwide; amyloid plaques and neurofibrillary tangles are the histopathological hallmarks of AD. We have recently reported that the inhibition of G9a/GLP complex promotes long‐term potentiation (LTP) and its associative mechanisms such as synaptic tagging and capture (STC). However, the role of this complex in plasticity impairments remains elusive. Here, we investigated the involvement of G9a/GLP complex in alleviating the effects of soluble Amyloid‐β 1‐42 oligomers (oAβ) on neuronal plasticity and associativity in the CA1 region of acute hippocampal slices from 5‐ to 7‐week‐old male Wistar rats. Our findings demonstrate that the regulation of G9a/GLP complex by inhibiting its catalytic activity reverses the amyloid‐β oligomer‐induced deficits in late‐LTP and STC. This is achieved by releasing the transcription repression of the brain‐derived neurotrophic factor (Bdnf) gene. The catalytic inhibition of G9a/GLP complex leads to the upregulation of Bdnf expression in the slices treated with oAβ. This further ensures the availability of BDNF that subsequently binds its receptor tyrosine kinase B (TrkB) and maintains the late‐LTP. Furthermore, the capture of BDNF by weakly activated synapses re‐establishes STC. Our findings regarding the reinstatement of functional plasticity and associativity in AD‐like conditions provide the first evidence for the role of G9a/GLP complex in AD. We propose G9a/GLP complex as the possible target for preventing oAβ‐induced plasticity deficits in hippocampal neurons.